STEPS OF DEVELOPING CREATIVITY IN STUDENTS IN TECHNOLOGY LESSONS - Aliboyev, Turgun (Mental Enlightenment Scientific-Methodological Journal, 2023)
The formation (development) of one or another quality in a person is a process that takes place in certain stages. The development of creative qualities in students is a step-by-step process. At each stage, specific tasks are solved in Hola based on the goal. In essence, the process of developing students' creative qualities takes place in four stages. Baskichlars have adaptation (adaptive), developmental, practical-active, analytical-evaluative character. The article talks about the specific aspects of the stages of development of creative qualities in students.